Damage caused by caterpillar of Helicoverpa armigera (Hübner, 1805) (Lepidoptera: Noctuidae) to soybean seedlings - Guazina, Renato Anastácio; Degrande, Paulo Eduardo; Souza, Ellen Patrícia; Gauer, Evandro (Revista de Ciências Agroveterinárias, 2019)
Soybean plants are susceptible to the attack of Helicoverpa armigera caterpillars throughout their cycle, including during early developmental stages, which can compromise their settling in the field. This study aimed to assess the damage caused by caterpillars to soybean seedlings. A randomized block design with five replicates was used and the treatments consisted of five levels of infestation: 0, 7, 14, 21 and 28 caterpillars/m-2. The infestation occurred in the cotyledon stage (VC), using fifth instar caterpillars. For three days, all damage caused to the stem, cotyledon, and unifoliates was evaluated. By the end of the experiment, seedling height, biomass, and the final stand value were determined. Damage was observed in the three vegetative structures and, in general, increase in insect population promoted higher levels of damage, reducing stand, height, and biomass of seedlings significantly. Thus, H. armigera caterpillars cause severe damage to soybean seedlings, which may affect their early establishment.